2017
DOI: 10.1007/s10681-017-1990-5
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and loci dissection for leaf epicuticular wax load and canopy temperature depression and their association with QTL for staygreen in Sorghum bicolor under stress

Abstract: Plant waxes and staygreen are distinct phenotypic traits that have been independently implicated in heat and drought tolerance among grasses. The association between these two traits has not been fully explored, which makes the exploitation of synergy between them difficult. This study assessed the association between QTL regulating the staygreen (Stg) trait in sorghum and those regulating epicuticular wax load (WL) and associated canopy temperature depression (TD). Using a recombinant inbred line (RIL) popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…The magnitude of variation in canopy temperature across the Setaria RIL population was similar to that observed for sorghum (Awika et al, 2017) and wheat (Mason et al, 2013) RIL populations. Variation in canopy temperature among the RIL population were similar on 30 DAS (wet 3.1 ˚C, dry 8.3 ˚C) and 32 DAS (wet 3.3 ˚C, dry 8.8 ˚C) and canopy temperature was correlated across the two dates sampled for both the wet (r = 0.78) and dry treatments (r = 0.66).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The magnitude of variation in canopy temperature across the Setaria RIL population was similar to that observed for sorghum (Awika et al, 2017) and wheat (Mason et al, 2013) RIL populations. Variation in canopy temperature among the RIL population were similar on 30 DAS (wet 3.1 ˚C, dry 8.3 ˚C) and 32 DAS (wet 3.3 ˚C, dry 8.8 ˚C) and canopy temperature was correlated across the two dates sampled for both the wet (r = 0.78) and dry treatments (r = 0.66).…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, improved methods for acquiring and analyzing images of stomatal guard cell complexes and other cell types in the epidermis are an area of active research (Haus et al, 2015;Dittberner et al, 2018;Fetter et al, 2019;Li et al, 2019). In addition, alternative approaches to rapidly screen stomatal conductance or rates of transpiration at the leaf and canopy scales (including temperature as a proxy) have also been developed and used to reveal genetic variation in traits related to drought stress and WUE (Liu et al, 2011;Bennett et al, 2012;Awika et al, 2017;Prado et al, 2018;Deery et al, 2019;Vialet-Chabrand and Lawson, 2019). However, the expected links between genetic variation in stomatal density and measures of water use, which would be expected in theory, are rarely tested and when tested, the results are inconsistent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yield potential and the metabolic fitness of crop plants under specific environmental conditions are determined by CTD (Kumari et al, 2013). A study on barley revealed a strong link between epicuticular leaf wax QTL and CTD, and that wax load influences plant canopy temperature (Awika et al, 2017). Based on phenotypic variation, CTD can act as a desirable criterion for heat-tolerant genotype selection (Mason and Singh, 2014).…”
Section: Canopy Temperature Depressionmentioning
confidence: 99%
“…For example, the DAS CC -associated SNP 36324_127 is located in Spo15232, which belongs to the basic leucine zipper transcription factor family proteins, members of which are involved in light and stress signaling influencing plant growth and development (Xiang et al, 2008). The marker 44291_137 (chr6, Position 45,352,029) resides in an intronic segment of the gene Spo11400, which codes for cytochrome P450 family protein, whose orthologs have been implicated in stay-green, photosynthesis, defense, and plant development (Cooper, 2000;Xu et al, 2015;Awika et al, 2017).…”
Section: Causative Snp-associated Putative Genes and Genomic Featuresmentioning
confidence: 99%